Effectiveness of aloe vera gel coating and paraffin wax-coated paperboard packaging on post-harvest quality of hog plum (Spondius mangifera L.) - Md Shakil; Sariful Islam; Sabina Yasmin; Md Sazzat Hossain Sarker; Fatehatun Noor (Heliyon, 2023)
In this research work, hog plum (Spondius mangifera L.) was treated with Aloe vera gel (AVG) coating and paraffin wax-coated box (PWB) packaging and stored at ambient condition (25 ± 3 °C and 80–85% relative humidity) for 12 d to evaluate their impact on postharvest quality and storability. The physicochemical properties, microbiological analysis, and decay evaluation were analyzed throughout the storage period. The AVG and PWB coating treatments both demonstrated a significant effect on the quality of fruits during storage. The results showed that fruits with AVG coating and PWB packaging exhibited lower decay rates, weight loss, color difference, total microbial population, total soluble solids, titratable acidity, and higher fruit firmness and pH than uncoated (control) fruits. The AVG coating was the most effective treatment, followed by the PWB packaging treatment. Our findings show that the AVG coating and PWB packaging treatment can be a promising solution for preserving the quality of hog plums and also helps in increasing the lifetime of hog plums during storage.